Pandangan Presiden Soeharto tentang Pancasila - Soeharto, 1921- (Yayasan Proklamasi, Centre for Strategic and International Studies, 1976)
The Indonesian president on Pancasila, state philosophy of Indonesia; selected passages from his speeches.